2002
DOI: 10.1002/bip.10172
|View full text |Cite
|
Sign up to set email alerts
|

Solution structure of a D,L‐alternating oligonorleucine as a model of double‐stranded antiparallel β‐helix

Abstract: Conformational characteristics of alternating D,L linear peptides are of particular interest because of their capacity to form transmembrane channels with different transport properties, as some natural antibiotics do. Single- and double-stranded beta-helical structures are common for alternating D,L peptides. The stability of the beta-helix depends on several structural factors, such as the backbone peptide length, type and position of side chains, and nature of terminal groups. The NMR and molecular dynamics… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2003
2003
2006
2006

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 28 publications
1
22
0
Order By: Relevance
“…Both experimental NMR data and molecular dynamics calculations indicate that the main conformation for this peptide is a dimeric antiparallel ␤-helix structure ␤ 5. 6 12. The observation of some NOEs correlations HN(i)-␣H(iϩ4) and the H-bonds network by ␦ HN and temperature coefficient values suggest a single ␤-helix structure ␤ 4.4 for the second conformation.…”
Section: Discussionmentioning
confidence: 97%
See 4 more Smart Citations
“…Both experimental NMR data and molecular dynamics calculations indicate that the main conformation for this peptide is a dimeric antiparallel ␤-helix structure ␤ 5. 6 12. The observation of some NOEs correlations HN(i)-␣H(iϩ4) and the H-bonds network by ␦ HN and temperature coefficient values suggest a single ␤-helix structure ␤ 4.4 for the second conformation.…”
Section: Discussionmentioning
confidence: 97%
“…In RMD calculations at 500 K, we found that the experimental restraints are only compatible with the model ␤ 5. 6 12, and that the calculation results are independent of the initial coordinates, as proved by the RMSD and energy values shown in Table V In order to analyze the dimer-monomer equilibrium, the effect of temperature was studied. The results obtained from the measurements at ten different temperatures fit well with the second-order Van't Hoff equation, as it is shown in Figure 5.…”
Section: 2mentioning
confidence: 99%
See 3 more Smart Citations